Analiza norm społecznych stanowiących podstawę kapitału społecznego. Na przykładzie badań w gminach wiejskich i miejsko-wiejskich województwa łódzkiego - Mularska-Kucharek, Monika (Zeszyty Wiejskie, 2013)
The aim of the article is the analysis of chosen social norms which are pivotal element of social capital creating, which is perceived as a chance to solve social and economical problems. Therefore the main subject of concern of this article are such social norms as, trust, subjectivity, reciprocity, veracity, allegiance and more precisely, the level of acceptance of these norms among the inhabitants of rural areas of Łódź Province.